Leitura de contos de suspense em Lygia Fagundes Telles - Santana, Ricardo Araujo Almeida (2023)
The present dissertation aims to carry out a study about the challenges of literary reading and the difficulties in the literacy process of ninth grade students of a municipal school in the city of Cícero Dantas, Bahia, between the pandemic years (2019-2022). As a final product, we will organize a storybook, containing literary reading workshops, from suspense tales by Lygia Fagundes Telles, taking into account the contributions of reception studies and literary literacy. Methodologically, the workshops explore different concepts of reading, such as subjective reading, by Annie Rouxel, who proposes a break with the traditional so that the student builds links between literature and life; cultural reading, by Carlos Gomes, who treats the literary text not only as an aesthetic object, but in its cultural and identity representations; and taking into account Rildo Cosson's reflections about the social-identity approach to literary reading, in which reading is never a solitary act, but a communion between the text and the meanings of the world. The work is divided into three main parts: the first concentrates the theoretical foundation, in which the main concepts of literary reading and literacy used in the research are theorized, as well as the methodological path followed, a brief history of the short story genre and the reactions of literature to gender issues; the second part presents the proposed intervention and the reorganization of the workshops; the third part describes the data analysis of the activities that were tested with the class. In the workshops, the short stories "The Ants", "Helga" and "Come see the sunset" were worked on, respectively following the structure of Pre-reading, Reading and Post-reading, in which subjective aspects, horizons of expectations, the characteristics of the suspense story genre and themes about gender violence will be observed. Next, with the help of the proposed methodologies and the theoretical foundations present in the references used in this study, it is hoped to return the focus to the readings of literary texts, and that the readings are experienced by the students, in the perspective that the readings contribute to their personal and social transformation.